Cover Image Volume 27, Issue 8. (August 2017) - Andersen, L. L.; Vinstrup, J.; Jakobsen, M. D.; Sundstrup, E.
Abstract : The cover image, by L. L. Andersen et al., is based on the Original Article Validity and reliability of elastic resistance bands for measuring shoulder muscle strength, DOI:10.1111/sms.12695 .